Sexual Self-Schemas, Sexual Dysfunction, and the Sexual Responses of Women with a History of Childhood Sexual Abuse - Rellini, Alessandra H. (Springer US, 2010)
Accumulating evidence points to the mediating effects of sexual self-schemas on the sexual difficulties of women with a history of childhood sexual abuse (CSA). The following study adds to the extant literature by investigating (1) sexual function and (2) sexual satisfaction utilizing validated measures, and reporting on the relationship between sexual self-schemas and physiological (vaginal photoplethysmography), subjective, and affective responses during laboratory exposure to sexual stimuli. In a community sample of women with (N = 48) and without (N = 48) a history of CSA, we tested (1) the mediation of negative affect on the relation between sexual self-schemas and sexual function/satisfaction, (2) the mediation of negative affect in the relation between CSA and sexual function/satisfaction, and (3) the mediation of sexual self-schemas in the relation between a history of CSA and negative affect prior to sexual stimuli. We found that more Embarrassed/Conservative and less Romantic/Passionate sexual self-schemas predicted negative affect prior to exposure to sexual stimuli which, in turn, predicted levels of sexual satisfaction. The lower sexual satisfaction of CSA survivors was partially mediated by higher reports of negative affect prior to sexual stimuli. However, negative affect prior to sexual stimuli was not mediated by the sexual self-schemas of CSA survivors. Thus, although sexual self-schemas predicted sexual satisfaction, they did not predict variance in negative affect prior to sexual videos experienced by women with a history of CSA.